High Viscous Fluid Transport Model - Tan, Ming Chai (Universiti Teknologi Petronas, 2004)
The purpose of this study is to develop a fluid flow model, which will describe the transport of high viscous fluid. For high viscous fluid, failure to account for radial variations in liquid viscosity may cause the pipeline pressure drop to be grossly under predicted. The procedures and techniques in modeling of the viscous fluid have been developed, and applied to real life practices. In this study, a set of mathematical equations was derived from the concepts of basic transport equations, namely the continuity, momentum and energy equations. This set of transport equations relates steady state flow and accounts for heat transfer. PIPEPHASE, a pipeline simulation tool, was used to model the flow of high viscous fluid. The results obtained was analyzed and compared with the high viscous fluid flow model developed from the mathematical equations. A solution algorithm was built to solve for the mathematical model. The Dulang D 8-L crude oil was selected as the high viscous fluid due to its viscous characteristic. The pipeline system used in the analysis was a typical pipeline system available in Sudan operating under Greater Nile Petroleum Operating Co. (GNPOC). All the data pertaining to the pipeline profile and fluid properties are obtained courtesy ofPETRONAS Research and Scientific Services (PRSS). The results obtained show that ordinary pipeline simulation tool under predicts the pressure drop by a factor of 1.5 to 2 depending on the flow rate. The model also shows how the dependency on liquid viscosity results in a bell shaped velocity profile rather than the parabolic Hagen-Poiseulle profile. n